The potential of sorghum meal as a replacement of corn meal in the diet for lactating buffaloes: impacts on milk yield and nutrient digestibility - Paola Pontieri; Luigi Del Giudice; Felicia Masucci; Antonio Di Francia; Claudia Lambiase; Grazia Scalera; Jacopo Troisi; Fadi Aramouni; Dmitriy Smolensky; Michael Tilley; Matteo Calcagnile; Pietro Alifano; et al. (Italian Journal of Animal Science)
Under the current climate change scenario and due to its lower irrigation water requirement, sorghum (Sorghum bicolour) meal has been proposed as a viable option in ruminant diet to replace corn meal. The aim of the present study was to evaluate animal performance and in vivo digestibility of lactating buffaloes fed a total mixed ration in which sorghum or corn meal was the primary energy source. Twenty multiparous buffaloes were equally divided into two balanced dietary groups fed the same basal diet supplemented with sorghum meal (Sorghum diet) or corn meal (Corn diet). After a 2–week adaptation period, feed intake and milk yield and components, including somatic cell count and coagulation characteristics, were recorded for 5 weeks. At the end of the experimental period, in vivo nutrient digestibility was assessed using acid insoluble ash as a marker of indigestibility. The use of sorghum meal did not negatively effect on dry matter intake, body weight, or body condition score. Milk yield did not differ between the diets, nor did the content of milk macro components and coagulation characteristics. However, milk urea concentration increased significantly (p < 0.05) in buffaloes fed the sorghum-based diet, indicating reduced dietary nitrogen utilisation. Additionally, these buffaloes exhibited a significant reduction in total tract starch digestibility (−2.8% points, p < 0.05) and a tendency towards lower crude protein digestibility (p = 0.06). We concluded that corn meal can be replaced by sorghum meal in the diet of lactating buffaloes without affecting their productive performance.